2012
DOI: 10.1007/s10792-011-9504-2
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured globe 20 years after radial and transverse keratotomy

Abstract: To report a case of corneal rupture due to blunt trauma occurring 20 years after radial keratotomy (RK) and transverse keratotomy. A 57-year-old woman sustained direct blunt trauma to her right eye. Ocular examination revealed a ruptured globe involving two of the eight RK incisions connected together across the visual axis with iris incarceration in the wound. The transverse keratotomy scars remained intact. The patient underwent primary corneal wound repair and iris repositioning. The postoperative period wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Poor results were often associated with severe injury, other eye injuries and delayed treatment. Unlike radial keratotomy (RK), where traumatic rupture of RK incisions can still occur after 20 years and there may be serious complications,17 ocular integrity after LASIK did not decrease as Peacock's study showed 18. Exaggeration of late traumatic flap complications after LASIK equal to those of RK is therefore unwise.…”
Section: Discussionmentioning
confidence: 98%
“…Poor results were often associated with severe injury, other eye injuries and delayed treatment. Unlike radial keratotomy (RK), where traumatic rupture of RK incisions can still occur after 20 years and there may be serious complications,17 ocular integrity after LASIK did not decrease as Peacock's study showed 18. Exaggeration of late traumatic flap complications after LASIK equal to those of RK is therefore unwise.…”
Section: Discussionmentioning
confidence: 98%
“…Wound dehiscence has also been reported after deep anterior lamellar keratoplasty,2 cataract surgery,3 penetrating globe injury and radial keratotomy 4. Trauma is the most common cause for dehiscence followed by early suture removal2 and increased intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%